An Overview of Current Solutions for Privacy in the Internet of Things - Yang, Guang (Frontiers in Artificial Intelligence, 2022)
As the Internet of Things (IoT) applications have been introduced into daily life, privacy issues have become significant concerns to users, network service providers, device producers, and related roles. This study provides a high-level introduction of current privacy-preserving solutions in IoT systems within the three phases of data collection, transmission, and storage. In these three phases, the following aspects were examined: 1.) security protocols at the physical and data link layers; 2.) network solutions; 3.) data storage and sharing approaches. Real-world implementations often involve more than one phase, and numerous technologies are combined to ensure privacy. Thus, an understanding of all phases and their technologies can be helpful for IoT research, design, development, and operation.